2014
DOI: 10.1016/j.foodhyd.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound treatment on the structural, physical and emulsifying properties of dairy proteins

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(65 citation statements)
references
References 44 publications
8
57
0
Order By: Relevance
“…It can be inferred that the aggregation of β‐lactoglobulin may be partially resulted from noncovalent interactions, such as electrostatic and hydrophobic interactions (Arzeni et al., ). Similar results had been obtained in the SDS‐PAGE studies of WPC, dairy proteins, and β‐lactoglobulin as reported previously (Chandrapala et al., ; O'Sullivan, Arellano, Pichot, & Norton, ).…”
Section: Resultssupporting
confidence: 90%
“…It can be inferred that the aggregation of β‐lactoglobulin may be partially resulted from noncovalent interactions, such as electrostatic and hydrophobic interactions (Arzeni et al., ). Similar results had been obtained in the SDS‐PAGE studies of WPC, dairy proteins, and β‐lactoglobulin as reported previously (Chandrapala et al., ; O'Sullivan, Arellano, Pichot, & Norton, ).…”
Section: Resultssupporting
confidence: 90%
“…O'Sullivan et al . () also observed an increase in size of egg white protein aggregation associated with thermal aggregation during US treatment.…”
Section: Resultsmentioning
confidence: 69%
“…The dissociation and aggregation of protein subunits play an important role in the microstructure, with consequent changes of functional properties such as rheology, emulsification and gelation (Durand, Gimel, & Nicolai, 2002;Nicorescu et al, 2010;O'Sullivan, Arellano, Pichot, & Norton, 2014). Li, Wang, Hu, and Liao (2014) reported that more intense high pressure CO 2 treatment caused the dissociation of larger aggregates and further aggregation in the smaller aggregates, which resulted in the change of polyphenol oxidase activity of thaumatin-like protein.…”
Section: Introductionmentioning
confidence: 99%